Characterization of deep-level defects in OFZ grown Nb-doped β-Ga2O3 single crystals - Ananthu Vijayan V L; Christopher A. Dawe; Sai Charan Vanjari; Vladimir P. Markevich; Matthew P. Halsall; Anthony R. Peaker; Moorthy Babu Sridharan; Martin Kuball (APL Materials)
This work explores niobium (Nb) as an n-type dopant in β-Ga2O3 substrates and examines potential defect states formed in single crystals grown using the optical floating zone (OFZ) technique. Crystals with 0.05 and 0.1 mol. % Nb source doping were analyzed, with x-ray diffraction (XRD) confirming a (100) orientation and full-width half-maximum (FWHM) values of 150 and 170 arc sec, respectively. The Hall measurements at 295 K revealed a free electron concentration of 6.1 × 1017 and 1.2 × 1018 cm−3 for 0.05 and 0.1 mol. % of Nb source doping, respectively. Defect characterization using deep-level transient spectroscopy (DLTS) provided insights into the deep-level defect states in the material, with this study presenting the first comprehensive defect analysis of Nb-doped β-Ga2O3 single crystals using Laplace-DLTS. Conventional-DLTS revealed a prominent deep-level trap E2 with activation energy for electron emission of 0.69 eV, while Laplace-DLTS resolved closely packed defect states within this E2 emission signal, identifying three distinct deep-levels: E2a (0.68 eV), E2b (0.71 eV), and E3 (0.89 eV). These defects are attributed to Fe and Ti impurities originating from the source material, with their presence in the samples confirmed by secondary ion mass spectrometry (SIMS). A surface-related defect (Es) with activation energy for electron emission of 0.28 eV is also identified. These findings highlight the need for ultra-high-purity source materials in improving the electrical properties of melt-grown β-Ga2O3, as doping compensation due to unintentional Fe incorporation from the source material could impact the electrical conductivity of the substrate.